BIOLOGICAL MARKERS OF THE Ki-67 CELL CYCLE AND Bcl-2 IN MYOMA, ADENOMYOSIS, AND LEIOMYOSARCOMA UTERI - Шрамко, Светлана Владимировна; Бондарев, Олег Иванович; Коваль, Елена Юрьевна; Лоскутова, Анна Юрьевна; Подтуркина, Татьяна Карловна; Шишея, Евгения Юрьевна; Станков, Алексей Иванович; Елдинова, Ольга Геннадьевна (Medicine in Kuzbass, 2019)
A comparative study of the expression of antibodies to the cell proliferative activity marker Ki-67 and antiapoptotic protein Bcl-2 in the tissue of leiomyosarcoma, ordinary uterine fibroids and cell uterine fibroids in isolated and associated with adenomyosis variants. Objective. 113 patients (32 patients with ordinary uterine fibroids, 26 patients with cell isolated uterine fibroids, 12 patients with isolated adenomyosis, 33 patients with uterine fibroids associated with adenomyosis, 10 patients with leiomyosarcoma of uterus). Methods. Pathohistological and immunohistochemical research into the tissue of uterus with determination of expression of antibodies to proteins Ki-67 and Bcl-2. Results. Spots of isolated adenomyosis and nodes of ordinary uterine fibroids are characterised by predominance of expression of antibodies to Bcl-2 over the level of expression to Ki-67. Predominance of Ki-67 indicators over Bcl-2 is determined in the tissue of leiomyosarcoma. The expression of markers of proliferative and antiapoptotic activity is determined as equal in spots of combined pathology and cell myomatous nodes. Conclusions: The growth of ordinary myomatous nodes and isolated adenomyosis is connected with suppression of apoptosis, progression of leiomyosarcoma of uterus is connected with increased proliferation. Equivalence of proliferation and apoptosis in cell nodes and uterine fibroids associated with adenomyosis testifies to multifactorial and little studied mechanisms of tissue growth, which can be considered as one of the reasons of compicated drug and surgical treatment and tendency to recurrence.